2014
DOI: 10.1016/j.radmeas.2014.02.018
|View full text |Cite
|
Sign up to set email alerts
|

OSL dosimetric properties of cerium doped lutetium orthosilicates

Abstract: This paper presents selected optically stimulated luminescence properties of Lu 2 SiO 5 :Ce single crystalline films grown using Liquid Phase Epitaxy technique. Comparison of continuous wave optically stimulated luminescence decay curves under blue and green light stimulation is shown. The dose response characteristic is found to be linear in the studied range from 100 Gy to 1 Gy. Analyses of the linearly modulated optically stimulated luminescence signal enabled establishing of the photoionization cross sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 9 publications
(11 reference statements)
0
5
0
Order By: Relevance
“…All results presented in this work were acquired from irradiation and readout of a 50×50×50$50\times 50\times 50$ mm 3$^3$ YSO:Ce crystal from Epic Crystal. This crystal is part of the oxyorthoscilicate (A 2$_2$ SiO 5$_5$, A=Lu,Y,Gd) scintillator family, which is known to exhibit OSL 24–28 and has recently been demonstrated to include a scintillator with an OSL light yield sufficiently high to enable 3D OSL‐based dosimetry 22,29 . The crystal was mounted in a custom‐made protective mount during all irradiations and readouts.…”
Section: Methodsmentioning
confidence: 99%
“…All results presented in this work were acquired from irradiation and readout of a 50×50×50$50\times 50\times 50$ mm 3$^3$ YSO:Ce crystal from Epic Crystal. This crystal is part of the oxyorthoscilicate (A 2$_2$ SiO 5$_5$, A=Lu,Y,Gd) scintillator family, which is known to exhibit OSL 24–28 and has recently been demonstrated to include a scintillator with an OSL light yield sufficiently high to enable 3D OSL‐based dosimetry 22,29 . The crystal was mounted in a custom‐made protective mount during all irradiations and readouts.…”
Section: Methodsmentioning
confidence: 99%
“…where T is total illumination time, which is ∼120 s here. Method of calculation of photoionization cross section (s) was described by Twardak et al [8]. Photoionization cross section is related to detrapping probability and maximum stimulation photon flux (J):…”
Section: Deconvolutionmentioning
confidence: 99%
“…Scintillators represent the forefront of room-temperature radiation detection and spectroscopy, and have also found applications for real-time beam imaging in the form of liquid scintillators [19,20]. Moreover, OSL properties have been reported in cerium-doped compounds of the lutetium orthosilicate scintillator family Lu(2-x)YxSiO5 (LYSO:Ce) [21][22][23], indicating that these scintillators could also be interesting for dosimetry. A recent study [24] found the OSL yield of commercial LYSO:Ce crystals to be high enough to enable high-spatial-resolution dose imaging in 3D for photon and electron excitation.…”
Section: Introductionmentioning
confidence: 99%